Fiscal Penal Code in the jurisprudence of the Constitutional Tribunal (in the period from 1999 to 2020) (Discourse of Law and Administration, 2022)
The publication refers to the issues of penal fiscal law in the jurisprudence of the Constitutional Tribunal. In the period under review, the Constitutional Tribunal issued 14 judgments,12 of which concerned substantive fiscal penal law, and 2 related to procedural fiscal penal law.Only in two cases the Constitutional Tribunal found that the provisions of the Fiscal Penal Code that were subject to constitutional review were inconsistent with the Polish Constitution. The conducted analysis of the jurisprudence leads to the conclusion that the main group of provisions subject to constitutional review are those which concern the traditional normative solutions typical of penal fiscal law. The Constitutional Tribunal has repeatedly emphasized that the different structure of the institutions shaping the substantive and procedural fiscal penal law against the background of common criminal law is not only justified, but also necessary. The position of the Constitutional Tribunal in this respect is uniform. It was not modified. As rightly pointed out, the Constitution of the Republic of Poland does not prevent different definition of the principles of liability and punishment for fiscal offenses and fiscal offenses from those specified in the Penal Code. This should be borne in mind when interpreting the provisions of the Fiscal Penal Code.